(untitled) (Revista Educação, Artes e Inclusão, 2023)
Considering the context of special education from the perspective of inclusive education, this article aims to discuss the use of assistive technologies (AT) in the teaching-learning process of high-ability students on the autism spectrum. Initially, for an overview, a questionnaire was applied, using the Google Forms tool, to professionals who work in Specialized Educational Services in Brazil. Its dissemination was carried out, in a broad way, on social networks and, also, by e-mail destined to strategic contacts of teaching institutions of Basic Education. From the answers collected from 32 professionals from nine Brazilian states (Maranhão, Tocantins, Espirito Santo, Paraná, São Paulo, Bahia, Ceará, Rio Grande do Sul, and Minas Gerais), it appears that part of some educators is not clear about the concept of TA. On the other hand, the answers point out that there is a great effort by these professionals to use them associated with other pedagogical resources, and some claim that it was possible to use them during the remote teaching imposed by the COVID-19 pandemic. Therefore, we were able to gather from the answers several examples of ATs in use in the respective schools and present a list of these ATs plus others found through bibliographic research aimed at high-ability students on the autism spectrum.